Dual Reciprocity Boundary Element Method for Steady Infiltration Problems from Furrow Irrigation Channels in Heterogeneous Soil - Muhammad Manaqib; Yanne Irene; Muhaza Liebenlito; Rizki Aulia ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
This research discusses solving the problem of infiltration of furrow irrigation channels in heterogeneous soil containing five soil layers using the Dual Reciprocity Boundary Element Method (DRBEM) numerical method. The mathematical infiltration model in furrow irrigation channels takes the form of the Richard Equation, which is transformed into a modified Helmholtz equation with mixed boundary conditions. Solving with DRBEM shows that in heterogeneous and homogeneous soils, the soil type influences the suction potential and water content values. Different soil depths in heterogeneous soil produce variations and jumps in suction potential and water content values in each soil layer.